1993
DOI: 10.1159/000227223
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of p53 Oncoprotein in Human Oral Squamous Cell Carcinomas and Leukoplakias: Comparison with Proliferating Cell Nuclear Antigen Staining and Correlation with Clinicopathological Findings

Abstract: Forty oral squamous cell carcinomas and 20 leukoplakias were examined for expression of p53 oncoprotein using an immunohistochemical technique with BP53-12 monoclonal antibody. Positive staining was found in 21/40 (52%) of the carcinomas and 2/20 (10%) of the leukoplakias. Furthermore, comparison of p53 expression with binding of PC 10 monoclonal antibody to proliferating cell nuclear antigen (PCNA) and degree of histological malignancy in terms of invasion and histological differentiation of carcinomas demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
1
6

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 3 publications
6
23
1
6
Order By: Relevance
“…Analysis of NLNR status showed no differences. Other data published evaluating the relationships between p-53 and TNM-stage, G-stage, tumor size and site, age and sex did not reveal any dependencies [1,13,21], although some studies have suggested such correlations [5,15,16]. The lack of TNM stage correlation with p-53 in our present study can reflect the number of subjects in a particular stage.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Analysis of NLNR status showed no differences. Other data published evaluating the relationships between p-53 and TNM-stage, G-stage, tumor size and site, age and sex did not reveal any dependencies [1,13,21], although some studies have suggested such correlations [5,15,16]. The lack of TNM stage correlation with p-53 in our present study can reflect the number of subjects in a particular stage.…”
Section: Discussioncontrasting
confidence: 68%
“…Others have demonstrated PCNA overexpression in precancerous lesions as well as in carcinomas in situ, progressing to invasive SCC [14,16]. We would speculate that in patients with LR after TL and initially negative lymph nodes the epithelium adjacent to the neoplasm underwent loss of control of cell proliferation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The functional inactivation of p53 protein plays a crucial role in the malignant transformation process. It provides the tumor cell with a higher capacity for division and proliferation [11]. A total of 21-49% of endometrial carcinomas show abnormal p53 expression [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…p53 expres sion was not related to the percentage of PCNA-labeled cells in this study. Some investigators have reported that p53 is correlated with PCNA [31][32][33][34][35][36]. Conversely, other groups found that there is no correlation between p53 and PCNA expression [37,38], The relationship between PCNA and p53 as shown by immunohistochemical analy sis remains controversial.…”
Section: Discussionmentioning
confidence: 99%